THE REINTEGRATION PROCESS OF PEOPLE WITH SCHIZOPHRENIA WHO REPEATED RELAPSE RETURN INTO THE COMMUNITY - Prasetyo, Franciscus Adi; Mufanti, Restu (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2022)
Abstract. The reintegration of people with schizophrenia to return to society often has to experience obstacles due to repeated relapses caused by multiple factors such as non-adherence to medication or certain social pressures that trigger the emergence of schizophrenia symptoms. The implications of recurrence are closely related to the decrease in the ability to carry out social functions, so they have the potential to lose their jobs, cannot continue their education, and have estranged social relations. There is a phenomenon that several people with schizophrenia who have had recurrent experiences can reintegrate into their social environment. Therefore, this study aims to describe the process of reintegration of people with schizophrenia who experience repeated relapses into society. The research method used is qualitative, with a case study approach on four people with schizophrenia living in four locations in Jakarta. The results of this study indicate that the two elements are operational and interrelated with each other. First, the main element is the individualistic internal process of people with schizophrenia which includes aspects of spirituality, cognition, and mental and social. Second, the enabling element, namely friends/friends and family who work to increase the chances of people with schizophrenia regaining self-stability to reintegrate into their social environment. Success in the social reintegration process allows people with schizophrenia to carry out their social functions as members of society, such as working, having a family, interacting naturally, and overcoming the fear of stigma and discrimination. Keywords: Relapse, Reintegration, People with Schizophrenia. Abstrak. Reintegrasi orang dengan skizofrenia untuk kembali ke masyarakat seringkali harus mengalami hambatan akibat kekambuhan berulang yang disebabkan oleh multifaktor seperti ketidakpatuhan minum obat atau tekanan sosial tertentu sehingga memicu munculnya gejala skizofrenia. Implikasi kekambuhan sangat erat kaitannya dengan penurunan kemampuan melaksanakan fungsi sosialnya sehingga berpotensi kehilangan pekerjaan, tidak dapat melanjutkan sekolah, dan kerenggangan hubungan sosial. Terdapat  fenomena sejumlah orang dengan skizofrenia yang memiliki pengalaman kambuhan, ternyata mampu terintegrasi kembali dengan lingkungan sosialnya. Oleh karena itu, penelitian ini bertujuan untuk mendeskripsikan tentang proses reintegrasi orang dengan skizofrenia yang mengalami kekambuhan berulang ke masyarakat. Metode penelitian yang dipergunakan adalah kualitatif dengan pendekatan studi kasus pada empat orang dengan skizofrenia yang berdomisili di empat lokasi berbeda di Jakarta. Hasil penelitian ini menyatakan bahwa terdapat dua elemen yang beroperasional serta saling berkaitan satu sama lain. Pertama, elemen utama yaitu proses internal orang dengan skizofrenia yang bersifat individualistik yang meliputi aspek spiritualitas, kognisi dan mental, serta sosial. Kedua, elemen pemungkin yaitu teman/sahabat dan keluarga yang bekerja untuk memperbesar peluang orang dengan skizofrenia meraih kembali stabilitas diri agar mampu terintegrasi kembali dengan lingkungan sosialnya. Keberhasilan dalam proses reintegrasi sosial memungkinkan orang dengan skizofrenia mampu melaksanakan kembali fungsi sosialnya sebagai anggota masyarakat seperti bekerja, berkeluarga, berinteraksi secara wajar dan mampu mengatasi ketakutan stigma dan diskriminasi.  Kata kunci: Kekambuhan, Reintegrasi, Orang Dengan Skizofrenia.